Changes in myocardial mechanics in patients with obesity following major weight loss after bariatric surgery. (26th July 2013) - Koshino, Yuki; Villarraga, Hector R.; Somers, Virend K.; Miranda, William R.; Garza, Carolina A.; Hsiao, Ju‐Feng; Yu, Yang; Saleh, Haydar K.; Lopez‐Jimenez, Francisco
<x xml:space="preserve">Abstract</x> Objective The purpose of this study was to evaluate myocardial mechanics in obese subjects using 2D‐speckle tracking echocardiography (2D‐STE). Design and Methods 63 obese individuals, including 28 who underwent bariatric surgery for weight loss (BMI 51 ± 9 kg/m2) and 35 managed conservatively (BMI 43 ± 7 kg/m2) were included. Changes in strain (S) and strain rate (SR) measured by 2D‐STE. Mean follow‐up was 23 ± 10 months. Results The surgery group had a significant weight loss (BMI 37 ± 10 kg/m2, P < 0.0001), but no change was noted in the nonsurgery group (BMI 42 ± 7 kg/m2, P = 0.1). For the surgery group, S and SR in early diastole (SRe) improved significantly in the longitudinal left ventricle (LV) (S: P = 0.0004, SRe: P = 0.02) and right ventricle (RV) (S: P = 0.02, SRe: P = 0.009), whereas no changes were seen in LV ejection fraction (LVEF). In the nonsurgery group, there was no change in S, SR, or body weight. For all patients, weight changes correlated significantly with changes in LV S (r = 0.43, P = 0.0005). Conclusions The improvement of S after bariatric surgery suggests that weight loss could improve myocardial performance, despite the lack of change in LVEF.